2002
DOI: 10.1097/00001648-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Measures of Sexual Activity and Prostate Cancer

Abstract: We conducted a meta-analysis of the association between prostate cancer and aspects of sexual activity. The data suggest an elevated relative risk (RR) of prostate cancer among men with a history of sexually transmitted infections. This was observed with both random- and fixed-effects models (RR = 1.4; 95% CI = 1.2-1.7; N = 17 studies; heterogeneity P = 0.14), especially for syphilis (RR = 2.3; 95% CI = 1.3-3.9; N = 6; heterogeneity P = 0.47). Risk of prostate cancer is also associated with increasing frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(181 citation statements)
references
References 38 publications
9
165
1
6
Order By: Relevance
“…Moreover, population studies have revealed an increased relative risk for development of prostate cancer in men with a prior history of sexually transmitted infections (Dennis and Dawson, 2002). These findings support the hypothesis that an infectious agent can be a potential cofactor in prostate cancer development.…”
supporting
confidence: 62%
“…Moreover, population studies have revealed an increased relative risk for development of prostate cancer in men with a prior history of sexually transmitted infections (Dennis and Dawson, 2002). These findings support the hypothesis that an infectious agent can be a potential cofactor in prostate cancer development.…”
supporting
confidence: 62%
“…Most studies adjusted for age, but none adjusted for sexual activity. Since an increased number of sexual partners and history of a sexually transmitted infection (STI) appear to be related to prostate cancer 9,17,21,22,35 but likely inversely related to having a vasectomy, this would cause negative confounding. The potential negative confounding would suggest that the pooled RR reported here is underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27] Overall, there is some suggestion from previous studies of an increased risk of prostate cancer with increased sexual frequency. 2 Reliability of sexual frequency in previous studies is unclear. In addition, only three previous studies looked at sexual frequency at different time periods and none looked at a potential lifetime cumulative effect.…”
Section: Reliability Of Sexual Historiesmentioning
confidence: 97%
“…15 A meta-analysis of prostate cancer and sexual activity found an increased risk of prostate cancer related to sexually transmitted infections, which was also supported by a weak but significant linear trend with increasing number of sexual partners. 2 If studies summarized in the meta-analysis suffered from nondifferential misclassification (random error) of sexual activity due to poor measurement, then the ORs reported would underestimate the association. If such were the case, then the statistically significant pooled OR of 1.2 for an increase in 20 partners 2 may actually be higher.…”
Section: Reliability Of Sexual Historiesmentioning
confidence: 99%
See 1 more Smart Citation